Pengaruh Pendekatan Realistic Mathematics Education (RME) Berproyek Terhadap Kemandirian Belajar Siswa (Indo-MathEdu Intellectuals Journal, 2025)
This research is based on the idea that student learning independence is something that can be developed through good learning. One of the learning that is suitable for increasing student learning independence is learning using the project-based RME approach. This study is a pre-experimental research with one group pretest and posttest design. The study was conducted on one group without a control or comparison group. The sample in this study is grade V students of SDN Gunasari. The instruments in this study are between student learning independence questionnaire and observation sheets. Quantitative data is processed in several stages, namely normality test, homogeneity test (if the data is normal) and data analysis is carried out using the Wilcoxon Signed Rank Test. The results of the study used a significance level = 0.05 (5%). The results of this study show that the project-based RME approach can increase students' learning independence